2006
DOI: 10.1242/jeb.02270
|View full text |Cite
|
Sign up to set email alerts
|

2-hydroxyestradiol-17β-induced oocyte maturation: involvement of cAMP–protein kinase A and okadaic acid-sensitive protein phosphatases,and their interplay in oocyte maturation in the catfishHeteropneustes fossilis

Abstract: SUMMARY In Heteropneustes fossilis, in vitro incubation of postvitellogenic follicles with 2-hydroxyestradiol-17β(2-OHE2, 5 μmol l–1) decreased significantly the total cAMP level, concomitant with germinal vesicle breakdown (GVBD). The incubation of the follicles with cAMP or cAMP-elevating drugs[phosphodiesterase (PDE) inhibitors], such as IBMX(3-isobutyl-1-methyl-xanthine), theophylline and caffeine, inhibited the 2-OHE2-induced GVBD in a concentration-dependent manner. The magnitude of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…It has been long time established that the decrease in cAMP levels is associated with reinitiation of oocyte maturation. It has also been shown in fish and amphibian that following hormonal stimulation, the level of intraoocyte cAMP decreased via the inhibition of adenylate cyclase activity (Sadler and Mailer 1983;Jordana et al 1984;Sadler and Maller, 1987;Mishra and Joy, 2006). The data of the present study demonstrate the involvement insulin alone can induced oocyte maturation in the catfish and that indicate causing the withdrawal of meiotic arrest in catfish oocyte in a dose dependent manner.…”
Section: Resultssupporting
confidence: 66%
“…It has been long time established that the decrease in cAMP levels is associated with reinitiation of oocyte maturation. It has also been shown in fish and amphibian that following hormonal stimulation, the level of intraoocyte cAMP decreased via the inhibition of adenylate cyclase activity (Sadler and Mailer 1983;Jordana et al 1984;Sadler and Maller, 1987;Mishra and Joy, 2006). The data of the present study demonstrate the involvement insulin alone can induced oocyte maturation in the catfish and that indicate causing the withdrawal of meiotic arrest in catfish oocyte in a dose dependent manner.…”
Section: Resultssupporting
confidence: 66%
“…Physiologically relevant concentrations of hydroxyestrogens, such as 2-OHE 2 , have been shown to induce OM by several mechanisms, including stimulation of maturation-inducing steroid production [30,33] and inhibition of aromatase activity, which would result in removal of the inhibitory effects of E 2 on OM [32]. The finding that total follicular cAMP was decreased during 5 lM 2-OHE 2 -induced OM in this species [28] raises the possibility that oocyte cAMP levels also may decrease after catecholestrogen treatment. Collectively, these studies in Indian catfish indicate that catecholestrogens induce OM through a nongenomic action, although the physiological relevance of the results with high 2-OHE 2 concentrations and the mechanisms of 2-OHE 2 actions remain unclear and warrant further investigation.…”
Section: Introductionmentioning
confidence: 61%
“…An interesting finding is that estrogen metabolites, mainly hydroxyestrogens, have an opposite action to that of E 2 in Indian catfish ovaries, 2-OHE 2 causing induction of OM at high concentrations (5 lM) [27][28][29] as well as at physiological concentrations (1-10 nM) [30]. Both periovulatory and seasonal changes in catecholestrogen concentrations and estrogen-2/4-hydroxylase activities have been observed in Indian catfish ovaries [27,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In alternative, 2-OHE 2 could work as an E 2 antagonist. Earlier studies showed that culturing catfish post-vitellogenic follicles in the presence of 1-20 μM 2-OHE 2 induced a 6-17-fold increase in the number of oocytes that resumed meiosis [22][23][24]62]. This improvement correlated with increased steroid production [63,64], inhibition of aromatase activity [65] and decreased follicular cAMP, which would result in the removal of the inhibitory effects of E 2 on oocyte maturation and meiotic resumption.…”
Section: Discussionmentioning
confidence: 96%
“…In teleosts (i.e., catfish and zebrafish), 2-OHE 2 has a crucial role as component of the gonadotrophin cascade of regulation of oocyte maturation and ovulation [22,23]. In vitro maturation of intact catfish follicles in the presence of 5 μM 2-OHE 2 increased significantly the frequency of oocytes attaining germinal vesicle breakdown (GVBD); instead, it did not change it when oocytes were cultured in the absence of surrounding follicle cells [24].…”
Section: Introductionmentioning
confidence: 99%